PENGARUH PEMBERIAN INSENTIF FINANSIAL DAN NONFINANSIAL TERHADAP KINERJA MELALUI KEPUASAN KERJA TENAGA KEPENDIDIKAN DI FAKULTAS KEDOKTERAN UNIVERSITAS AIRLANGGA SURABAYA - jurnalpps pps; Ainul Huri; Cathrine Sri Hartati; Woro Utari (Prodi Magister Manajemen Universitas Wijaya Putra, 2020)
ABSTRACT Companies or institutions usually need to pay attention to giving incentives to employees. The size of the increased aid funds provides encouragement in supporting employees. The purpose of this research is to study the planning of providing financial and non-financial incentives to work satisfaction planning at the Faculty of Medicine, Airlangga University. This research uses quantitative research data. The type of data used is primary data obtained from the distribution of questionnaires containing several questions about Educational Personnel at Airlangga University, Surabaya. Data were analyzed using the path analysis statistical method. From the results of this study it can be concluded based on the results of the path analysis obtained direct financial incentive variables on the performance of employees or education personnel. The financial incentive variable and the non-financial incentive variable do not support the workforce performance through employee job satisfaction or education personnel. Keyword : incentive, financial, non financial